2021
DOI: 10.1371/journal.pone.0249521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental feeding on the fecal bacterial communities of Rocky Mountain elk in the Greater Yellowstone Ecosystem

Abstract: Supplemental feeding of wildlife is a common practice often undertaken for recreational or management purposes, but it may have unintended consequences for animal health. Understanding cryptic effects of diet supplementation on the gut microbiomes of wild mammals is important to inform conservation and management strategies. Multiple laboratory studies have demonstrated the importance of the gut microbiome for extracting and synthesizing nutrients, modulating host immunity, and many other vital host functions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Previous studies of different types of mammals have revealed that their fecal microbiota and function cluster according to diet (herbivores, omnivores, and carnivores) rather than host phylogeny (Ley et al, 2008;Muegge et al, 2011). The microbiome composition of Rocky Mountain elk (Cervus canadensis nelsoni) that was supplied with alfalfa pellets changed compared to that in natural feed population (Couch et al, 2021b). In captive primates, gut microbiota cluster weakly by species, but strongly by diet, so that the gut microbiota is more similar when monkeys in the same genus are fed with the same diet, even if they are different species (Hale et al, 2018;Huan et al, 2020).…”
Section: Do Microbes Show Convergence Inmentioning
confidence: 99%
“…Previous studies of different types of mammals have revealed that their fecal microbiota and function cluster according to diet (herbivores, omnivores, and carnivores) rather than host phylogeny (Ley et al, 2008;Muegge et al, 2011). The microbiome composition of Rocky Mountain elk (Cervus canadensis nelsoni) that was supplied with alfalfa pellets changed compared to that in natural feed population (Couch et al, 2021b). In captive primates, gut microbiota cluster weakly by species, but strongly by diet, so that the gut microbiota is more similar when monkeys in the same genus are fed with the same diet, even if they are different species (Hale et al, 2018;Huan et al, 2020).…”
Section: Do Microbes Show Convergence Inmentioning
confidence: 99%
“…Similarly, agricultural conversion has limited the availability of high-quality winter resources for elk, which serve as reservoir hosts of Brucella abortus (Figure 2C). Large elk populations are now supported by lower-quality supplemental feeding, which reduces migration and promotes high-density aggregations, thereby increasing the spread of Brucella among these animals and potentially spillover to livestock [87][88][89][90] . Climate change may further exacerbate loss of phenological diversity and interrelated shifts in animal movement; however, this has not been explicitly linked to zoonotic spillover 91 .…”
Section: Llmentioning
confidence: 99%
“…Taxonomic profiling involves quantifying the identity and abundance of the microbial taxa present in a sample [37]. By comparing taxonomic profiles of microbiomes sampled from individuals, populations or species subject to different conditions, such as climatic shifts [8], pollution [35], and captive management actions [16], it is possible to infer how these factors affect the microbiome and which host species may be most negatively affected. Comparing the taxonomic profiles of communities can also help explain how an individual's microbiome develops in response to environmental conditions and external microbial communities.…”
Section: Taxonomic Profilesmentioning
confidence: 99%
“…This example demonstrates how effective microbe-targeted conservation efforts can be at preserving biodiversity on a macro level. A study in elk (Cervus canadensis) also used this approach to show that supplementary feeding of populations with processed alfalfa pellets led to a shift in gut microbiome composition, whereas supplementation with unprocessed loose hay had no effect [16].…”
Section: Taxonomic Profilesmentioning
confidence: 99%
See 1 more Smart Citation